2021
DOI: 10.31219/osf.io/8pg45
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trends in HIV Stigma Experienced by People Living with HIV in the Netherlands: A Comparison of Cross‐Sectional Surveys Over Time

Abstract: We investigated whether HIV stigma in the Netherlands has changed in recent years. We compared data on stigma settings and manifestations from 2007 (n = 667) and, specifically for the health care sector, 2009 (n = 262), to data acquired in 2019 and 2020 (n = 258). Results showed reductions in stigma from friends, family, acquaintances, at work, in the financial services sector, and in media. However, stigmatizing messages in media remained highly prevalent. Stigma in the LGBTQI+ community, with sexual partners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…A recent large international study spanning 25 countries found that 13.0% of people with HIV have recently experienced stigma and discrimination from their healthcare providers associated with their HIV status [14]. This experienced stigma increased considerably when seeking care for non-HIV-related health problems [15,16]. Stigma and discrimination mostly manifested as verbal abuse, gossip, denial of services, and disclosing a patients' HIV status without consent [14,15].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent large international study spanning 25 countries found that 13.0% of people with HIV have recently experienced stigma and discrimination from their healthcare providers associated with their HIV status [14]. This experienced stigma increased considerably when seeking care for non-HIV-related health problems [15,16]. Stigma and discrimination mostly manifested as verbal abuse, gossip, denial of services, and disclosing a patients' HIV status without consent [14,15].…”
mentioning
confidence: 99%
“…This experienced stigma increased considerably when seeking care for non-HIV-related health problems [15,16]. Stigma and discrimination mostly manifested as verbal abuse, gossip, denial of services, and disclosing a patients' HIV status without consent [14,15]. A recent Dutch study on the perspectives of people with HIV showed an increase in HIV stigma in Dutch healthcare settings over the past decade [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation